The Significance of Diversified Farms in Improving the Reclaiming Condition of Soil Lands - Bakhytgul Zhumabaevna Kurbaniyazova; Rano Maksetbaevna. Dzhumatova (Genius Publishing Group, 2022)
The article analyzes the importance of diversified farms in improving land reclamation, increasing the efficiency of their land use, restoring soil fertility, and their role in economic development
Keywords: land reclamation, restoring soil fertility, economic development